Students’ Perceptions of Using Class Dojo in a Teaching and Learning Process - Pratista, Ganang Yudha (Universitas Nusantara PGRI Kediri, 2023)
In the present educational context, the teaching and learning process is gradually associated with computers to maximize its outcomes. One of the platforms which is commonly used is ClassDojo. Implementing the principles of gamification, ClassDojo is considered effective to motivate students to be more active in online classes, pushes healthy competitiveness, and enhances learning and enjoyment. This study aims to investigate the students’ perceptions of using ClassDojo in the teaching and learning process. This study applied a cross-sectional survey design in which 77 participants range from 17 to 23 years of age. To assess the perceptions, a close-ended questionnaire with five-point Likert scale was distributed and then analyzed to find out its average. Then, several interviews were carried out as the data triangulation. The result shows that there are two main components of ClassDojo which motivates students in the English class; points and avatars. The students are more motivated and engaged in the teaching and learning process as they strive to earn more points. In addition, the students are eager to customize their own character and enjoy playing it throughout the class. Thus, not only points, avatars are also the essential component of ClassDojo which motivates and engages the students in the teaching and learning process.